Social harmonization in the eyes of Polish stakeholders: In search of consensus - Karolina Beaumont; Katarzyna Mirecka; Izabela Styczyńska (Center for Social and Economic Research (CASE), 2016)
Aspects of labor mobility and discrepancies in social benefits schemes in Member States became an urgent matter to address. Revision of the Posting of Workers Directive, the European Pillar of Social Rights and the European Mobility Package were aimed at introducing more harmonization within the EU countries. However, the EU propositions faced a strong resistance from some groups of stakeholders and Member States. Moreover, the debate has been evolving quickly given recent events such as the economic and migration crises and Brexit. CASE held a forum with various Polish stakeholders, where CASE experts gathered views on the future of social situation in the EU. They are all summarized in this Policy Brief. Main policy recommendations emphasize that proposed legislation is important for Poland, however it still needs more debate, since under current form certain policies might be harmful for many EU Member States.
Keywords: J31; J32; J61; H53; 330; posted workers; labor mobility; social harmonization; social model; social rights; social convergence; labor market